PEMIKIRAN TENTANG PENDIDIKAN DALAM HADIST NABI - Muhammad Rizal Rifa’i; Ika Setiawati (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This article examines the Prophet Muhammad's thoughts on education in his hadith, which are the main source for developing the concept of Islamic education. The research method used is library research with content analysis. Hadith not only serve as normative guidelines, but also present a practical approach to education that is comprehensive, covering spiritual, intellectual, moral, and social aspects. The goal of Islamic education is to develop a complete human being, one who has a balance between morals and knowledge. This study focuses on the obligation to seek knowledge and character building based on the values of the hadith. The educational process exemplified by the Prophet involved various methods such as lectures, question and answer sessions, experiments, and demonstrations that were able to reach the humanity of the students. Important values such as honesty, trustworthiness, humility, and compassion are emphasized in Islamic education. Lifelong education is also an important point in the hadith, which is in line with the concept of continuous learning in modern education systems. The Prophet's hadith serve as the basis for integrative and transformative values in developing an Islamic education system that is relevant to the needs of the times.